2014
DOI: 10.1007/s11999-013-3381-0
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Bone Ingrowth and Attachment Strength for Stability of Percutaneous Osseointegrated Prostheses

Abstract: Background Percutaneous osseointegrated prosthetic (POP) devices have been used clinically in Europe for decades. Unfortunately, their introduction into the United States has been delayed, in part due to the lack of data documenting the progression of osseointegration and mechanical stability.Questions/purposes We determined the progression of bone ingrowth into porous-coated POP devices and established the interrelationship with mechanical stability. Methods After amputation, 64 skeletally mature sheep receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…98 Additionally, recent studies by Jeyapalina et al confirmed that when an immediate-loading protocol was used with percutaneous OI implants placed within the intramedullary canal, there were no signs of implant loosening postoperatively for up to 1 year. 63,[99][100][101] The appositional bone index, calculated at predetermined time points, demonstrated progressive bone interconnection and further validated the importance of "fit and fill" (Figure 5). These findings provide further evidence for an immediate implant loading once primary implant stability has been achieved.…”
mentioning
confidence: 61%
“…98 Additionally, recent studies by Jeyapalina et al confirmed that when an immediate-loading protocol was used with percutaneous OI implants placed within the intramedullary canal, there were no signs of implant loosening postoperatively for up to 1 year. 63,[99][100][101] The appositional bone index, calculated at predetermined time points, demonstrated progressive bone interconnection and further validated the importance of "fit and fill" (Figure 5). These findings provide further evidence for an immediate implant loading once primary implant stability has been achieved.…”
mentioning
confidence: 61%
“…It was found that anatomic shape of the implant and the surgical protocols helped to achieve and maintain at least five contact/ apposition zones (Table 3) throughout the length of the each implant. It was believed that these contact zones, mainly at the distal regions, might provide the initial stability to prevent micromotion-related implant loosening and help to achieve the robust osseointegration, which was demonstrated by pullout strength data in a related study [16]. The absence of radiolucent and neocortex formation within this porous region, observed in 12-month radiographs, indicated that the implant was osseointegrated within this region.…”
Section: Discussionmentioning
confidence: 81%
“…10) present within the fluted region of these specimens further confirmed implant fixation by regional osseointegration. Although the implant was intentionally porous coated to a length of only 1 cm of structure at the distal end, the pullout strength study of this device showed extremely robust osseointegration with approximately 1000-N pullout at Time 0 and exceeding 13,000 N at 12 months [16]. If this attachment strength can be achieved in the human situation, this particular POP design would likely be bone sparing in the event of revision surgeries that require implant removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous OI systems rely on adequate initial fixation, and circumferential fill of the medullary canal, for bone ingrowth and long‐term stability (Engh et al, ; Shelton et al, ; Jeyapalina et al, ; Al Muderis et al, ). Additionally, such systems must be compatible with placement at multiple locations along the bone to accommodate variable amputation levels.…”
mentioning
confidence: 99%